Overexpression of rRNA genes in a patient with intellectual disability and familial 13p+ chromosome - I. S. Kolesnikova; A. A. Tulupov; A. A. Dolskiy; M. A. Lemskaya; A. A. Savelov; E. D. Petrovsky; A. A. Antonov; Yu. V. Maksimova; A. R. Shorina; I. G. Sergeeva; A. S. Telepova; A. S. Graphodatsky; et al. (Бюллетень сибирской медицины)
A study of a child with intellectual disability revealed an enlarged p-arm in chromosome 13 and amplified rDNA. qRT-PCR showed an approximately 6-fold increased level of rRNA in the patient’s blood samples. fMRI study revealed changes in uncinate fasciculus. His father is a carrier of the same chromosome, healthy and has a normal level of rRNA.